Clinical Outcomes of the Traditional Latarjet Versus the Congruent Arc Modification for the Treatment of Recurrent Anterior Shoulder Instability: A Meta-analysis. Issue 10 (12th October 2021) - Mengers, Sunita R.P.; Knapik, Derrick M.; Kaufman, Matthew W.; Edwards, Gary; Voos, James E.; Gillespie, Robert J.; Karns, Michael R.
Background: Few studies have compared clinical outcomes between the traditional Latarjet procedure for anterior shoulder instability and the congruent arc modification to the Latarjet procedure. Purpose: To systematically evaluate the literature for the incidence of recurrent instability, clinical outcomes, radiographic findings, and complications for the traditional Latarjet procedure and the congruent arc modification and to compare results of each search. Study Design: Systematic review; Level of evidence, 4. Methods: A systematic review and meta-analysis was conducted according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. We included studies published between January 1990 and October 2020 that described clinical outcomes of the traditional Latarjet and the congruent arc modification with a follow-up range of 2 to 10 years. The difference in surgical technique was analyzed using a chi-square test for categorical variables, while continuous variables were evaluated using a Student t test. Results: In total, 26 studies met the inclusion criteria: 20 studies describing the traditional Latarjet procedure in 1412 shoulders, and 6 studies describing the congruent arc modification in 289 shoulders. No difference between procedures was found regarding patient age at surgery, follow-up time, Rowe or postoperative visual analog scores, early or late complications, return-to-sport timing, or incidence of improper graft placement or graft fracture. A significantly greater proportion of male patients underwent glenoid augmentation using the congruent arc modification versus traditional Latarjet ( P < .001). When comparing outcomes, the traditional Latarjet procedure demonstrated a lower incidence of fibrous union or nonunion ( P = .047) and broken, loose, or improperly placed screws ( P < .001), and the congruent arc modification demonstrated improved outcomes with regard to overall return to sport ( P < .001), return to sport at the same level ( P < .001), incidence of subluxation ( P = .003) or positive apprehension ( P = .002), and revision surgery for recurrent instability ( P = .027). Conclusion: Outcomes after the congruent arc modification proved at least equivalent to the traditional Latarjet procedure in terms of recurrent instability and return to sport, although early and late complications were equivalent. The congruent arc procedure may be an acceptable alternative to traditional Latarjet for the treatment of anterior shoulder instability with glenoid bone loss; however, long-term outcomes of this procedure are needed.